Emergency Centre-based paediatric procedural sedation: current practice and challenges in Cape Town. (2nd January 2019) - Burger, A; Hodkinson, PW; Wallis, LA
Abstract : Background: The aims and objectives of this survey of the current practice of doctors working in Emergency Centres (ECs) in the Cape Town metropole was to assess clinical practice and attempt to identify obstacles to the practice of paediatric procedural sedation and analgesia (PPSA). This was considered essential to establish a baseline for quality assurance purposes and improvement. Methods: After institutional ethics approval, a cross-sectional descriptive study was performed in 25 ECs in both private and government sectors in Cape Town. Specific aspects of PPSA practice were analysed after the anonymous completion of a specifically designed questionnaire, by full-time doctors working at each EC. The doctors' grade and training, practice preferences, medication and use of monitoring, and any perceived challenges to performing PPSA were assessed. Results: Sixteen ECs agreed to be part of the study and 62 questionnaires were completed (a 64% response rate). Procedural sedation and analgesia was performed at all the participating ECs, by medical practitioners of varying experience. Doctors' awareness of unit protocols was inconsistent. Common indications were orthopaedic interventions, radiological investigations and surgical procedures. Medications used were similar in the responding units, but dosages varied. Monitoring was poor compared with local and international standards. The obstacles reported predominantly related to a lack of training and formal protocols. Conclusions: This study was the first to evaluate the practice of Emergency Centre paediatric procedural sedation and analgesia practice in a South African setting. The lack of a formal system of training and accreditation, for both doctors and facilities, and the need for institutional and nationwide PPSA guidelines were highlighted.